If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (9 + -1u)(3u + -5) = 0 Reorder the terms: (9 + -1u)(-5 + 3u) = 0 Multiply (9 + -1u) * (-5 + 3u) (9(-5 + 3u) + -1u * (-5 + 3u)) = 0 ((-5 * 9 + 3u * 9) + -1u * (-5 + 3u)) = 0 ((-45 + 27u) + -1u * (-5 + 3u)) = 0 (-45 + 27u + (-5 * -1u + 3u * -1u)) = 0 (-45 + 27u + (5u + -3u2)) = 0 Combine like terms: 27u + 5u = 32u (-45 + 32u + -3u2) = 0 Solving -45 + 32u + -3u2 = 0 Solving for variable 'u'. Factor a trinomial. (-9 + u)(5 + -3u) = 0Subproblem 1
Set the factor '(-9 + u)' equal to zero and attempt to solve: Simplifying -9 + u = 0 Solving -9 + u = 0 Move all terms containing u to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + u = 0 + 9 Combine like terms: -9 + 9 = 0 0 + u = 0 + 9 u = 0 + 9 Combine like terms: 0 + 9 = 9 u = 9 Simplifying u = 9Subproblem 2
Set the factor '(5 + -3u)' equal to zero and attempt to solve: Simplifying 5 + -3u = 0 Solving 5 + -3u = 0 Move all terms containing u to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -3u = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -3u = 0 + -5 -3u = 0 + -5 Combine like terms: 0 + -5 = -5 -3u = -5 Divide each side by '-3'. u = 1.666666667 Simplifying u = 1.666666667Solution
u = {9, 1.666666667}
| 2w+17=43 | | h=-16t^2+77t+77 | | x(x+8)=180 | | 112-6x=12x+18 | | 12-4x=15-3x | | 5x^2+37+42=0 | | 6x+9y=36 | | 5x^2+37=-42 | | 3-1.2y=2.4 | | 8x^(7/2)-24=0 | | 7/2y-1+13 | | m=-0.5(29)+23 | | 5x+3=19+5 | | 2x^2+18=90 | | 4x^2-31x+21=0 | | 9-7x=90-28x | | 159-2x=34x+23 | | 2(3x+4)=4x-2 | | x(2x-1)*(3x+2)=0 | | x^4-24x^3+144x^2=0 | | 8+2x+3-x=2x-1 | | 4x-12x+9=0 | | x^4-24x^3+14x^2=0 | | -39+r=26 | | =4y^3-4y^2+3-y | | 11-8x=147-36x | | (7x^2)+24=54 | | x^3+x=332.5 | | (20+p)+(3p-23)+p=552 | | 11x=3x^2-4 | | 45=3(w-36)+30 | | X+x+12+x+x+12=x+11+x+11+x+16 |